Analysis of the male annual antler cycle, reproductive behavior and spotted fawn presence in the tropical white-tailed deer - Rodríguez-Ramírez, Miguel; Mora, Jose Manuel (THERYA, 2022)
The rutting season of the white-tailed deer (Odocoileus virginianus) is seasonal in North America, but in tropical latitudes it occurs year-round with peaks locally variable. Reproductive cycle of this species in Costa Rica is variable, clearly seasonal in San Lucas Island but continuous with two birth peaks in Palo Verde and Santa Rosa national parks in northwestern Costa Rica. In Hacienda y Refugio de Vida Silvestre Curú in the Nicoya Peninsula, a site south of these parks but in a different life zone, we observed males with hard antlers in 2015 but only from July to November. We therefore hypothesized that white-tailed deer have a continuous reproductive cycle during the year in Curú because the rainfall pattern is the same as in Palo Verde and Santa Rosa. We visited Curú every month and recorded the status of white-tailed deer antler growth: nubs, velvet, and hard, from January 2016 to December 2019. We also recorded other rut behaviors and the presence of spotted fawns. We recorded 1,134 observations of the status of antler growth, 13 observations on reproductive behavior and 133 observations of spotted fawns. The antler cycle was seasonal in the four years of study. Male antler casting took place from mid-November to mid-February and the growth of new antlers began in mid-December and lasted until mid-March. Velvet shedding occurred in April, May and June, and by July males had hard antlers. The rutting season lasted three months from mid-June to mid-August. Small spotted fawns were observed from the middle of the dry season to the beginning of the rainy season. All this highly contrasts with the reproduction pattern observed in Santa Rosa. Lack of seasonal variation in the photoperiod is likely an important factor that allows deer to reproduce throughout the year in these protected areas, but this variation does not exist in Curú either, where the species is seasonal. The reproductive patterns of white-tailed deer in Central and South America may have evolved in response to seasonal fluctuations in specific food availability, competition, or predation, all of which may be directly related to rainfall patterns. Greater knowledge of the link between rainfall patterns and food availability for deer would be of great help to further our understanding of factors driving the reproduction cycle of the White-tailed deer.